(3x-1)(4x+5)=(4x+5)(2x-1)

Simple and best practice solution for (3x-1)(4x+5)=(4x+5)(2x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x-1)(4x+5)=(4x+5)(2x-1) equation:


Simplifying
(3x + -1)(4x + 5) = (4x + 5)(2x + -1)

Reorder the terms:
(-1 + 3x)(4x + 5) = (4x + 5)(2x + -1)

Reorder the terms:
(-1 + 3x)(5 + 4x) = (4x + 5)(2x + -1)

Multiply (-1 + 3x) * (5 + 4x)
(-1(5 + 4x) + 3x * (5 + 4x)) = (4x + 5)(2x + -1)
((5 * -1 + 4x * -1) + 3x * (5 + 4x)) = (4x + 5)(2x + -1)
((-5 + -4x) + 3x * (5 + 4x)) = (4x + 5)(2x + -1)
(-5 + -4x + (5 * 3x + 4x * 3x)) = (4x + 5)(2x + -1)
(-5 + -4x + (15x + 12x2)) = (4x + 5)(2x + -1)

Combine like terms: -4x + 15x = 11x
(-5 + 11x + 12x2) = (4x + 5)(2x + -1)

Reorder the terms:
-5 + 11x + 12x2 = (5 + 4x)(2x + -1)

Reorder the terms:
-5 + 11x + 12x2 = (5 + 4x)(-1 + 2x)

Multiply (5 + 4x) * (-1 + 2x)
-5 + 11x + 12x2 = (5(-1 + 2x) + 4x * (-1 + 2x))
-5 + 11x + 12x2 = ((-1 * 5 + 2x * 5) + 4x * (-1 + 2x))
-5 + 11x + 12x2 = ((-5 + 10x) + 4x * (-1 + 2x))
-5 + 11x + 12x2 = (-5 + 10x + (-1 * 4x + 2x * 4x))
-5 + 11x + 12x2 = (-5 + 10x + (-4x + 8x2))

Combine like terms: 10x + -4x = 6x
-5 + 11x + 12x2 = (-5 + 6x + 8x2)

Add '5' to each side of the equation.
-5 + 11x + 5 + 12x2 = -5 + 6x + 5 + 8x2

Reorder the terms:
-5 + 5 + 11x + 12x2 = -5 + 6x + 5 + 8x2

Combine like terms: -5 + 5 = 0
0 + 11x + 12x2 = -5 + 6x + 5 + 8x2
11x + 12x2 = -5 + 6x + 5 + 8x2

Reorder the terms:
11x + 12x2 = -5 + 5 + 6x + 8x2

Combine like terms: -5 + 5 = 0
11x + 12x2 = 0 + 6x + 8x2
11x + 12x2 = 6x + 8x2

Solving
11x + 12x2 = 6x + 8x2

Solving for variable 'x'.

Reorder the terms:
11x + -6x + 12x2 + -8x2 = 6x + 8x2 + -6x + -8x2

Combine like terms: 11x + -6x = 5x
5x + 12x2 + -8x2 = 6x + 8x2 + -6x + -8x2

Combine like terms: 12x2 + -8x2 = 4x2
5x + 4x2 = 6x + 8x2 + -6x + -8x2

Reorder the terms:
5x + 4x2 = 6x + -6x + 8x2 + -8x2

Combine like terms: 6x + -6x = 0
5x + 4x2 = 0 + 8x2 + -8x2
5x + 4x2 = 8x2 + -8x2

Combine like terms: 8x2 + -8x2 = 0
5x + 4x2 = 0

Factor out the Greatest Common Factor (GCF), 'x'.
x(5 + 4x) = 0

Subproblem 1

Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0

Subproblem 2

Set the factor '(5 + 4x)' equal to zero and attempt to solve: Simplifying 5 + 4x = 0 Solving 5 + 4x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 4x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 4x = 0 + -5 4x = 0 + -5 Combine like terms: 0 + -5 = -5 4x = -5 Divide each side by '4'. x = -1.25 Simplifying x = -1.25

Solution

x = {0, -1.25}

See similar equations:

| y-4x+3=17 | | 6x^2-14x-12=0 | | 7(x-2)+5x=6(2x+5)-10 | | 3(4x-2)=28 | | (8+2x)(12+2x)=96 | | 1.50(203-y)+2.50y=372.50 | | 4x^2+40x=0 | | 2x-6=2x+11 | | 3a^2-12=0 | | 5t-8=16-t | | x+2x(x+10)=12-5x | | 9(a-14)+2(a+41)=a+1 | | 4x+2+7x-14=1-9(x+1) | | (x+30)=3 | | 7(a-4)+2(a+12)=a-8 | | y=18z | | 7x^2=7-8x | | -7x-2=8x+13 | | 80=2(x+2)+2(4x-10) | | 12-2p=q | | 3=x+x+x | | 4x-(3x+8)=5 | | 1.6x=.7x | | 19-4e+7e=106 | | 4x-4=-32 | | 4X^2+4X+13=0 | | -18=-7y+3(y+2) | | 6(5x-8)-20=11(2x-3)+3x | | 2n^2+4n+1=0 | | 2+3x=-13 | | 16y^3-2=y-32y^2 | | 5x=15-2(x+7) |

Equations solver categories